Papular acrodermatitis of childhood (the Gianotti-Crosti disease): an Australia antigen disease - Öztürk, Mustafa K.; Özsoylu, Şinasi; Köse, Galip (The Turkish Journal of Pediatrics, 1978)
An eight year old boy with Gianotti’s disease is described and new concept for its pathogenesis is shortly reviewed.